Smart Bilayer Polyacrylamide/DNA Hybrid Hydrogel Film Actuators Exhibiting Programmable Responsive and Reversible Macroscopic Shape Deformations. Issue 42 (28th September 2020) - Bi, Yanhui; Du, Xiaoxue; He, Pingping; Wang, Chunyan; Liu, Chang; Guo, Weiwei
Abstract: As a crucial instinct for the survival of organisms, adaptive smart deformation has been well shown via profusely astounding examples within biological morphogenesis in nature, which inspired the construction of biomimetic shape‐morphing materials with controlled actuating behaviors. Herein, the construction of nature‐inspired bilayer hydrogel film actuators, composed of a polyacrylamide hydrogel passive layer and a polyacrylamide‐DNA hybrid hydrogel active layer, which exhibited programmable stimuli‐responsive and reversible macroscopic shape deformations directed by the sequence of DNA crosslinking units in the active layer, is reported. As a proof‐of‐concept, the introduction of DNA i‐motif based crosslinking structures into the active layer, which can undergo pH‐stimulated formation and dissociation of crosslinking between polymers and therefore change the crosslinking density of the active layer, lead to the redistribution of the internal stresses within the bilayer structure, and result in the pH‐stimulated shape deformations. By programming the sequence of DNA units in the active layer, a Ag + /Cysteamine‐stimulated bilayer DNA hybrid hydrogel film actuator is further constructed and exhibits excellent actuation behaviors. Thanks to the micrometer‐scale thickness of the films, these actuators exhibit a high degree of macroscopic and reversible shape deformations at high speed, which may find use in future smart biosensing and biomedical applications. Abstract : Programmable stimuli‐responsive bilayer DNA hybrid hydrogel film actuators that can undergo reversible and macroscopic shape deformations at high speed are fabricated. By programming the sequences of incorporated DNA units, actuators that can respond to pH changes or the presence of metal ion/ligand stimuli are developed, which may have potential in future smart biosensing and biomedical applications.